2011
DOI: 10.1073/pnas.1102226108
|View full text |Cite
|
Sign up to set email alerts
|

Visualization of the nanospring dynamics of the IκBα ankyrin repeat domain in real time

Abstract: IκBα is a crucial regulator of NFκB transcription. NFκB-mediated gene activation is robust because levels of free IκBα are kept extremely low by rapid, ubiquitin-independent degradation of newly synthesized IκBα. IκBα has a weakly folded ankyrin repeat 5-6 (AR5-6) region that is critical in establishing its short intracellular half-life. The AR5-6 region of IκBα folds upon binding to NFκB. The NFκB-bound IκBα has a long half-life and requires ubiquitintargeted degradation. We present single molecule FRET evide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
61
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(69 citation statements)
references
References 39 publications
7
61
1
Order By: Relevance
“…Moreover, studies on the six ankyrin repeat protein IB␣ show it also has a weakly folded C terminus. Here, repeats five and six fold upon binding to their cognate partner (the transcription factor NF-B) (29,30). It has been shown that the function and lifetime within the cell of IB␣ is critically linked to whether this region is structured via ligand binding or not (31).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, studies on the six ankyrin repeat protein IB␣ show it also has a weakly folded C terminus. Here, repeats five and six fold upon binding to their cognate partner (the transcription factor NF-B) (29,30). It has been shown that the function and lifetime within the cell of IB␣ is critically linked to whether this region is structured via ligand binding or not (31).…”
Section: Discussionmentioning
confidence: 99%
“…The created sample chamber was then filled with an aqueous solution of 167 mM APS for 30 min and rinsed with DI water, resulting in a glass surface modified with primary amine groups. The APS coverslips were functionalized with a 1:100 Mal-PEG-SVA/mPEG-SVA molar mixture (31,32) by incubation for 1 h in 0.1 M sodium bicarbonate buffer, pH 8.5 (33). Bubbles were removed from the sodium bicarbonate buffer by vortexing and ultrasonication.…”
Section: Total Internal Reflection Fluorescence Microscopy Imagingmentioning
confidence: 99%
“…Developments in optical and force spectroscopy techniques have enabled single-molecule studies on several aspects of protein dynamics, folding, and interactions (34, 35). Single-molecule techniques provide new types of information at very low sample concentrations without ensemble averaging (35)(36)(37)(38)(39)(40)(41)(42). Using the distance dependence of single-molecule Förster/fluorescence resonance energy transfer (smFRET) to probe protein dimensions, we studied the effect on α-synuclein of urea and TMAO, both as individual cosolvents and also in varying mixing ratios.…”
mentioning
confidence: 99%